2016
DOI: 10.1007/s00276-016-1767-x
|View full text |Cite
|
Sign up to set email alerts
|

The oblique occipital sinus: anatomical study using bone subtraction 3D CT venography

Abstract: Many anatomical variations in the oblique occipital sinus can be seen on CT venography. Some OOSs function as the main drainage route of the intracranial veins instead of the TS. Thus, careful examination is essential for preoperative evaluation in posterior fossa lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…It has been reported that the OV is more prominent in patients with thrombosis [20]. If the TS and SS are hypoplastic, the OV is used as an alternative outflow pathway [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the OV is more prominent in patients with thrombosis [20]. If the TS and SS are hypoplastic, the OV is used as an alternative outflow pathway [9].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the occipital sinus are important for neurosurgical planning in the posterior cranial fossa and deviation from the expected midline location should be reported. If the occipital sinus deviates from the midline and joins a sigmoid sinus inferolaterally, it is known as an oblique occipital sinus (Fig B–D) . Superiorly, an oblique sagittal sinus communicates with the confluence of sinuses, transverse sinus, straight sinus, or superior sagittal sinus .…”
Section: Dural Venous Sinus Variations and Related Pathologymentioning
confidence: 99%
“…If the occipital sinus deviates from the midline and joins a sigmoid sinus inferolaterally, it is known as an oblique occipital sinus (Fig B–D) . Superiorly, an oblique sagittal sinus communicates with the confluence of sinuses, transverse sinus, straight sinus, or superior sagittal sinus . An oblique sagittal sinus can be uni‐ or bilateral and associated with hypoplastic transverse (Fig C and D) and/or sigmoid sinuses …”
Section: Dural Venous Sinus Variations and Related Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The patent OS can rarely run off the midline, over the cerebellar convexity dura, and communicate with the SS, and such entity is called an “oblique OS ” [4]. In a CT-angiography study on 1,805 patients, Shin et al [5] found the oblique OS incidence to be 2.3%. A persistent large OS could present a hazardous surgical challenge.…”
Section: Introductionmentioning
confidence: 99%